3D screen printing technology enables fabrication of oral drug dosage forms with freely tailorable release profiles - Enke, Marcel; Schwarz, Nicolle; Gruschwitz, Franka; Winkler, Daniela; Hanf, Felix; Jescheck, Lisa; Seyferth, Stefan; Fischer, Dagmar; Schneeberger, Achim (International Journal of Pharmaceutics, 2023)
3D printing offers new opportunities to customize oral dosage forms of pharmaceuticals for different patient populations, improving patient safety, care, and compliance. Although several notable 3D print technologies have been developed, such as inkjet printing, powder-based printing, selective laser sintering (SLS) printing, and fused deposition modelling (FDM), among others, their capacity is often limited by the number of printing heads. 3D screen-printing (3DSP) is based on a classic flatbed screen printing that is widely used in industrial applications for technical applications. 3DSP can build up thousands of units per screen simultaneously, enabling mass customization of pharmaceuticals. Here, we use 3DSP to investigate two novel paste formulations: immediate-release (IR) and extended-release (ER) using Paracetamol (acetaminophen) as the active pharmaceutical ingredient (API). Both disk-shaped and donut-shaped tablets were fabricated using one or both pastes to design drug delivery systems (DDS) with tailored API release profiles. The size and mass of the produced tablets demonstrated high uniformity. Characterization of the tablets physical properties, such as breaking force (25–39 N) and friability (0.002–0.237%), adhering to Ph. Eur (10th edition). Finally, drug release tests with a phosphate buffer at pH 5.8 showed Paracetamol release depended on the IR- and ER paste materials and their respective compartment size of the composite DDS, which can be readily varied using 3DSP. This work further demonstrates the potential of 3DSP to manufacture complex oral dosage forms exhibiting custom release functionalities for mass production.
CRIS-Team Scopus Importer:2023-06-30
Keywords: 3D printing; 3D screen printing; Additive manufacturing; Controlled release; Drug delivery system; Extended-release; Immediate-release; Paracetamol